2016
DOI: 10.1002/jssc.201600895
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of moluodan concentrated pill using high‐performance liquid chromatography fingerprinting coupled with chemometrics

Abstract: In this study, a fast and effective high-performance liquid chromatography method was developed to obtain a fingerprint chromatogram and quantitative analysis simultaneously of four indexes including gallic acid, chlorogenic acid, albiflorin and paeoniflorin of the traditional Chinese medicine Moluodan Concentrated Pill. The method was performed by using a Waters X-bridge C reversed phase column on an Agilent 1200S high-performance liquid chromatography system coupled with diode array detection. The mobile pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As for compounds which had low content, especially Ginseng Radix et Rhizoma, Rehmanniae Radix, and Poria, or were difficult to be completely separated, we used LC-MS/MS to quantify them. The candidate ingredients were chosen based on the references of pertinent herbs, including the following 14 chemical components: XS and XZ from the minister medicine of Xanthii fructus [ 21 ]; JA and JB from the minister medicine of Ziziphi Spinosae Semen [ 22 ]; MPA from the minister medicine of Ophiopogonis Radix [ 23 ]; RD from the minister medicine of Rehmanniae Radix [ 24 ]; GRF, GRG, GRR, and GRB from the minister medicine of Ginseng Radix et Rhizoma [ 25 ]; DA, PAC, and ATA from the adjuvants medicine of Poria [ 26 ]; and PX from adjuvants medicine of the guide medicine of Polygalae Radix [ 27 ]. The chemical structures of the 25 compounds are shown in Figure S5 .…”
Section: Resultsmentioning
confidence: 99%
“…As for compounds which had low content, especially Ginseng Radix et Rhizoma, Rehmanniae Radix, and Poria, or were difficult to be completely separated, we used LC-MS/MS to quantify them. The candidate ingredients were chosen based on the references of pertinent herbs, including the following 14 chemical components: XS and XZ from the minister medicine of Xanthii fructus [ 21 ]; JA and JB from the minister medicine of Ziziphi Spinosae Semen [ 22 ]; MPA from the minister medicine of Ophiopogonis Radix [ 23 ]; RD from the minister medicine of Rehmanniae Radix [ 24 ]; GRF, GRG, GRR, and GRB from the minister medicine of Ginseng Radix et Rhizoma [ 25 ]; DA, PAC, and ATA from the adjuvants medicine of Poria [ 26 ]; and PX from adjuvants medicine of the guide medicine of Polygalae Radix [ 27 ]. The chemical structures of the 25 compounds are shown in Figure S5 .…”
Section: Resultsmentioning
confidence: 99%
“…The mobile phase was composed of 70% methanol (A) and 30% water (B) with a 0.8 mL/min eluent velocity, under a detection temperature of 30 °C. The UV detection wavelength of GA was set at 254 nm. The UV detection wavelength of Res was set at 306 nm. The content of GA was calculated according to the standard curve ( y = 18666 x – 67.804, R adj 2 = 0.9999). The content of Res was calculated according to the standard curve ( y = 71002 x + 65.388, R adj 2 = 0.9999).…”
Section: Methodsmentioning
confidence: 99%
“…The developing solvent systems, such as ethyl acetate/formic acid/acetic acid/water, ethyl acetate/nbutanol/ acetic acid/water, butyl acetate/formic acid/acetic (12), isoquercitrin (13), wogonin (15), and genkwanin (16) acid/water with different ratios were investigated on the RP system. Results showed that the appropriate R f values and entire separation of four compounds obtained by developing solvent system of ethyl acetate/formic acid/acetic acid/water (10:1.5:1.5:1.0, v/v/v/v).…”
Section: Optimization Of Hptlc Analysismentioning
confidence: 99%
“…Up to now, a few methods have been reported to evaluate the quality of TCM [15][16][17][18][19][20][21]. For Herba Leonuri, the authentication and quantification of stachydrine and leonurine using normal-phase (NP) and reversed-phase (RP) chromatographic methods has been adopt in Chinese Pharmacopoeia (2015 edition) [22].…”
mentioning
confidence: 99%